2020
DOI: 10.3390/foods9111551
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Authentication of 100% Italian Durum Wheat Pasta by FT-NIR Spectroscopy Combined with Chemometric Tools

Abstract: Italy is the country with the largest durum wheat pasta production and consumption. The mandatory labelling for pasta indicating the country of origin of wheat has made consumers more aware about the consumed pasta products and is influencing their choice towards 100% Italian wheat pasta. This aspect highlights the need to promote the use of domestic wheat as well as to develop rapid methodologies for the authentication of pasta. A rapid, inexpensive, and easy-to-use method based on infrared spectroscopy was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Metabolic fingerprinting is used without preliminary identification of individual metabolites [11]. De Girolamo [12] simplifies the strategy to determine the authentification product become two strategies, targeted and untargeted analytical approaches. Targeted analytical approaches are specific to adulterant and their quantification, e.g., LC-MS and GC-MS. Untargeted analytical offer minimal information about the type of adulterant and focus on the classification of unknown products as belonging to the class of authentic product or not, e.g., NIR, MR, and Raman spectroscopy [13].…”
Section: Techniques To Discriminate Product Authenticitymentioning
confidence: 99%
“…Metabolic fingerprinting is used without preliminary identification of individual metabolites [11]. De Girolamo [12] simplifies the strategy to determine the authentification product become two strategies, targeted and untargeted analytical approaches. Targeted analytical approaches are specific to adulterant and their quantification, e.g., LC-MS and GC-MS. Untargeted analytical offer minimal information about the type of adulterant and focus on the classification of unknown products as belonging to the class of authentic product or not, e.g., NIR, MR, and Raman spectroscopy [13].…”
Section: Techniques To Discriminate Product Authenticitymentioning
confidence: 99%
“…Dilek et al [ 44 ] used the FTIR method to detect fumonisins due to Fusarium niger contaminated raisins and demonstrated that Fusarium niger contaminated raisins showed an increased absorbance in the characteristic bands at 1733 cm −1 , 1736 cm −1 , and 1708 cm −1 , demonstrating that the FTIR spectroscopy technique is capable of determining fumonisins and other mycotoxins in agricultural products. Annalisa et al [ 45 ] used Fourier transform near-infrared (FT-NIR) and Fourier transform mid-infrared (FT-MIR) spectra combined with chemometrics for the first time to detect deoxynivalenol (DON) in wheat bran samples. Standard normal variables (SNV) transformation, mean normalization, and other preprocessing methods were used to compare and fuse the processed spectral data.…”
Section: Application Of Infrared Spectroscopy Technology In Detection...mentioning
confidence: 99%
“…True positives True positives + False positives (5) Recall = True positives True positives + False Negatives ( 6) A Vis-NIR Spectroscopy was used to determine how millet varieties differ in how some incident radiation is reflected, transmitted, and absorbed. As presented in Figure 1, the emitted energy produced a series of stripes and a few peaks.…”
Section: Precision =mentioning
confidence: 99%
“…The food traceability system, which the European Union officially recognized (E.U.) in 2000, is an essential tool for protecting consumers against contamination [5]. Keeping foods free of contamination and illustrating the complete identification of products receives significant attention in many countries.…”
Section: Introductionmentioning
confidence: 99%